1, 3-dichloro-2-propanol induced hepatic lipid accumulation by inhibiting autophagy via AKT/mTOR/FOXO1 pathway in mice. (November 2021) - Fan, Yong; Lu, Jing; Liu, Jinhua; Zhang, Ranran; Yu, Zelin; Guan, Shuang
Abstract: Our study investigated the effects of food contaminant 1, 3-dichloro-2-propanol (1, 3-DCP) on hepatic lipid metabolism and its mechanism. We found that triglyceride (TG), total cholesterol (TC) and the number of lipid droplets (LDs) were increased in the liver of C57BL/6 mice given intragastric administration of 1, 3-DCP for 30 days. Meanwhile, 1, 3-DCP inhibited autophagosomes and lysosomes formation, reflected by decreased LC3-II, LAMP1, LAMP2, CTSD, CTSB expression, increased p62 expression and decreased LC3 fluorescence. Subsequently, we detected the changes of hepatic lipid accumulation caused by 1, 3-DCP using an autophagy inducer or inhibitor. In vivo, Hepatic lipid accumulation caused by 1, 3-DCP was mitigated by the autophagy inducer Rapa. On the contrary, the autophagy inhibitor (chloroquine or 3-methyladenine) further exacerbated hepatic lipid accumulation caused by 1, 3-DCP. 1, 3-DCP reduced the number of autophagosomes encapsulated LDs, assessed by colocalization of LD and LC3. These data demonstrated that 1, 3-DCP induced lipid accumulation by inhibiting autophagy. We further investigated the mechanism of 1, 3-DCP-inhibited autophagy and found 1, 3-DCP increased the ratios of p-AKT/AKT, p-mTOR/mTOR, p-FOXO1/FOXO1, decreased FOXO1 nuclear localization in vivo . These proteins may be involved in the regulation of 1, 3-DCP-mediated autophagy. We detected the changes in autophagy marker protein LC3-II and lipid accumulation using an AKT inhibitor ARQ-092 or a mTOR inhibitor rapamycin in HepG2 cells. Compared with 1, 3-DCP group, lipid accumulation was decreased, LC3-II and FOXO1 nuclear localization were increased, p-FOXO1 levels were decreased in HepG2 cells pretreated with ARQ-092 or rapamycin. Taken together, these data revealed that the effects of 1, 3-DCP on lipid accumulation by inhibiting autophagy were dependent on AKT/mTOR/FOXO1 signaling pathway. Our study not only supplied the mechanism of 1, 3-DCP toxicity, but also provided experimental basis for effective intervention measures of 1, 3-DCP toxicity. Highlights: 1, 3-DCP induced hepatic lipid accumulation in mice. 1, 3-DCP inhibited hepatic autophagy flux in mice. 1, 3-DCP induced hepatic lipid accumulation by inhibiting lipophagy in mice. 4.1, 3-DCP inhibited autophagy through AKT/mTOR/FOXO1 pathway in HepG2 cells.